A comprehensive investigation and analysis of the cognitive status and management status of stress related disorders of nursing staff in burn unit (医院烧伤科护理人员对应激相关障碍的认知情况及管理现状的综合调查分析) - HUA Ying (华英); WU Changqing (吴长青); CHEN Yarong (陈亚蓉); ZHANG Yi (张怡) (中西医结合护理)
Objective To study the comprehensive survey results of the cognitive status and management status of stress-related disorders among nursing staff in the burn unit of the hospital. Methods From January 2020 to June 2020, 103 nursing staff in burn unit of tertiary grade A general hospital were selected as the research objects by convenient sampling method. Baseline data, management status and cognition of all subjects were evaluated by the questionnaire on the cognitive status of stress-related disorders for nursing staff in the burn department. Univariate and multivariate linear regression analysis was used to identify the cognitive factors of the subjects. Results Among 103 nursing staff with mental disorders, 59. 22% would invite professional psychologists or psychiatrists for consultation, 28. 16% would not necessarily, 12. 62% would not; 84 nursing staff indicated that there was no stress related disorder assessment tool in their department, accounting for 81. 55%; 74 nursing staff showed no stress related disorder nursing routine, accounting for 71. 84%; 60 nursing staff had not received trauma related psychological nursing training, accounting for 58. 25%; 49 nursing staff said that the department carried out psychological nursing unconditionally, accounting for 47. 57%. The univariate analysis showed that age, professional title, employment form and training were closely related to the cognitive status of stress-related disorders of nursing staff in hospital burn department (P < 0. 05). However, the working years and educational level were not related to the cognitive status of stress-related disorders of nursing staff in hospital burn department (P＞0. 05). Multiple linear regression analysis showed that the professional title and the training were the influencing factors of the nursing staff's cognition of stress-related disorders (P < 0. 05). Conclusion The cognitive status of nurses in hospital burn department is not optimistic, and the management status needs to be improved. Professional title and the training experience were the influencing factors of the nursing staff's cognition of stress-related disorders, which are worthy of clinical attention. (目的 调查医院烧伤科护理人员对应激相关障碍的认知情况及管理现状。方法 2020年1月—6月通过便利抽样法选取三级甲等综合医院烧伤科103例护理人员作为研究对象。通过烧伤科护理人员对应激相关障碍认知情况问卷调查表对所有受试者的基线资料、管理现状以及认知情况进行评估。并通过单因素、多因素多元线性回归分析明确研究对象对应激相关障碍的认知影响因素。结果 103例护理人员中遇到精神障碍患者会邀请专业心理医生或精神科医生会诊占比59. 22%(61/103), 不一定占比28. 16%(29/103), 不会占比12. 62%(13/103); 84例护理人员表示所在科室无应激相关障碍的评估工具, 占比81. 55%; 74例护理人员表示所在科室无应激相关障碍护理常规, 占比71. 84%; 60例护理人员表示未接受过创伤相关心理护理培训, 占比58. 25%; 49例护理人员表示科室无条件开展心理护理, 占比47. 57%。单因素分析显示, 年龄、职称、聘用形式及接受过培训与否均和医院烧伤科护理人员对应激相关障碍的认知情况密切相关(P＜0. 05); 而工作年限、文化程度均和医院烧伤科护理人员对应激相关障碍的认知情况无关(P＞0. 05)。多元线性回归分析结果显示, 职称及接受过培训与否均是医院烧伤科护理人员对应激相关障碍的认知影响因素(P＜0. 05)。结论 医院烧伤科护理人员对应激相关障碍的认知情况不容乐观, 且管理现状有待提高。职称及接受过培训与否均是医院烧伤科护理人员对应激相关障碍的认知影响因素, 值得临床重点关注。)